Pengaruh Budaya Kaizen Dan Reward Terhadap Kinerja Karyawan PT. Seino Indomobil Logistic Mojokerto - Permana, Muhammad Novian Adi; Setyariningsih, Eny; Kasnowo (PT. Kreasi Karya Majakata, 2024)
This study was conducted to analyze the influence of Kaizen culture and reward on employee performance at PT. Seino Indomobil Logistics Kantor Project PT. Pabrik Kertas Tjiwi Kimia Mojokerto. The research methodology uses a quantitative approach with data collection techniques through questionnaires to 80 employees. The sampling technique uses saturated sampling. The results of data analysis show that Kaizen culture has a positive and significant influence on employee performance, with a t value of 5,956 (p = 0.000). Reward has a positive and significant influence on employee performance, with a t value of 3.164 (p = 0.002). Kaizen culture and reward together have a positive and significant effect on employee performance, with a calculated F value of 17,735 (p = 0.000). These findings indicate that the implementation of Kaizen culture and reward can improve employee performance at PT. Seino Indomobil Logistics Kantor Project PT. Pabrik Kertas Tjiwi Kimia Mojokerto